Learning progressions/trajectories in mathematics: Supporting reform at scale. Issue 3 (November 2021) - Siemon, Dianne
In recent years, attention has turned to the development of evidenced-based learning progressions/trajectories as a means of identifying the likely paths learners might take in developing a deep, well-connected understanding of key aspects of mathematics. However, the extent to which this work influences what happens in mathematics classrooms varies greatly depending on the prevailing relationship between curriculum, pedagogy and assessment. This article will draw on current policy documents and the literature to challenge current assumptions at the national level about what constitutes a learning progression. It will draw briefly on the results of a recently completed, large-scale study on mathematical reasoning in the middle years of schooling to make a case for evidenced-based learning progressions/trajectories as boundary objects in reconnecting and rebalancing the curriculum, pedagogy and assessment relationship to support reform at scale.